2022
DOI: 10.1007/s40119-022-00254-w
|View full text |Cite
|
Sign up to set email alerts
|

Expert Recommendations on the Usage of Non-vitamin K Antagonist Oral Anticoagulants (NOACs) from India: Current Perspective and Future Direction

Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs) are a new class of anticoagulant drugs used in the prevention and treatment of venous thromboembolism (VTE) and atrial fibrillation (AF). Anticoagulation requires the integration of the correct type and dose of oral anticoagulants based on patient characteristic, and therefore therapy needs to be individualized for each patient. Growing scientific evidence from studies on NOACs has led to a better understanding of their benefits and safety. A large amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Even though more than a third of our subjects reported concurrent antiplatelet or aspirin use, the influence of coulcerogenic medication did not compromise the preventative efficacy of the PPI in NOAC-PPI cotherapy. As evidenced by prior research, the combination of NOACs with either aspirin or antiplatelets does not increase the risk of UGIB 1 . In addition, underlying comorbidities or concomitant medications predicted to increase ulcer risk at baseline were less prevalent in our patients receiving NOAC monotherapy, and these factors had no influence on UGIB risk.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Even though more than a third of our subjects reported concurrent antiplatelet or aspirin use, the influence of coulcerogenic medication did not compromise the preventative efficacy of the PPI in NOAC-PPI cotherapy. As evidenced by prior research, the combination of NOACs with either aspirin or antiplatelets does not increase the risk of UGIB 1 . In addition, underlying comorbidities or concomitant medications predicted to increase ulcer risk at baseline were less prevalent in our patients receiving NOAC monotherapy, and these factors had no influence on UGIB risk.…”
Section: Discussionmentioning
confidence: 75%
“…Nonvitamin K oral anticoagulants (NOACs) are innovative agents generated in a cascade by thrombin inhibitors or direct factor Xa inhibitors. Numerous studies have shown that NOACs are effective in both the prevention and treatment of venous thromboembolism 1 6 . NOACs are gaining popularity because of their rapid onset and offset of action, predictable pharmacodynamics that reduce the need for routine therapeutic monitoring, and fewer dietary or drug interactions in comparison to warfarin 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The main methods of preventing venous thrombosis include medication, physical therapy and exercise therapy. [18][19][20][21] Although long-term anticoagulation reduces the incidence of deep-vein thrombosis, patients are at increased risk of local bleeding and cerebral hemorrhage. 22,23 Physiotherapy is effective, but not convenient due to the limitations of space and equipment.…”
Section: Introductionmentioning
confidence: 99%